2018
DOI: 10.1108/jfm-06-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

ICT-based system for Malaysian residential maintenance projects – literature review

Abstract: Purpose This paper aims to identify the different system approach that is equipped with decision making processes. Presently, most maintenance organisations are still implementing conventional methods rather than fully integrated information and communication technology (ICT) to manage the information database on maintenance of residential building. The significant factor to select an ICT is much more advantageous than just a way to improve interfirm communication and cooperation on maintenance management proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…3.2.2 Lack of Information and Communications Technology (ICT). Organisations of maintenance must update their system with the advancement of current information and communications technology (ICT) to support the procedures of maintenance processes and the proposed solution to maintenance decision-making, productivity and solving problems (Wahid, 2012;Ali et al, 2016;Ismail, 2017aIsmail, , 2018. Lack of communication technology and software tools through building maintenance practices contributes to the failure of the maintenance process or in delay of maintenance works (Ismail, 2014(Ismail, , 2017aAli et al, 2016) Ismail (2014 and Ismail (2017a) conclude that organisations of building maintenance that have adopted communications technology for their maintenance management process face fewer maintenance problems compared to those with limited or with no communication technology.…”
Section: Building Maintenance Practices Issues and Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…3.2.2 Lack of Information and Communications Technology (ICT). Organisations of maintenance must update their system with the advancement of current information and communications technology (ICT) to support the procedures of maintenance processes and the proposed solution to maintenance decision-making, productivity and solving problems (Wahid, 2012;Ali et al, 2016;Ismail, 2017aIsmail, , 2018. Lack of communication technology and software tools through building maintenance practices contributes to the failure of the maintenance process or in delay of maintenance works (Ismail, 2014(Ismail, , 2017aAli et al, 2016) Ismail (2014 and Ismail (2017a) conclude that organisations of building maintenance that have adopted communications technology for their maintenance management process face fewer maintenance problems compared to those with limited or with no communication technology.…”
Section: Building Maintenance Practices Issues and Effectsmentioning
confidence: 99%
“…Consequently, an inappropriate decision related to maintenance planning goes to the lowest proposed opportunity of organisation productivity and quality Ali et al, 2016;Ismail, 2017b). Effective software can suggest the best decision, which can improve organisation's productivity and quality (Ali et al, 2016;Ismail, 2017bIsmail, , 2018. Thus, maintenance organisations must use maintenance software tools to improve organisation productivity and to solve their problems.…”
Section: Building Maintenance Practices Issues and Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature highlighted that the utilization of tools, techniques and technology is a must since it would ensure the effectiveness and sustainability of the MM program [51,52]. From the case studies, it was observed that there were several efforts existed towards integrating the MM program with relevant tools, techniques and technology.…”
Section: -6-application Of Tools Technique and Technologymentioning
confidence: 99%
“…The adopted synthesis of good practice in the maintenance index framework is based on the findings from a review of literature on heritage building maintenance projects. This paper is part of a larger study, and only introduces the overall framework (Ismail, 2018). The relevant components are described in the following sections.…”
Section: System Architecturementioning
confidence: 99%